Serum and alveolar procalcitonin had a weak diagnostic value for ventilator-associated pneumonia in patients with pulmonary infection score ≥ 6 - Shokri Mehran; Ghasemian Roya; Bayani Masomeh; Maleh Parviz Amri; Kamrani Masoumeh; Sadeghi-; Ebrahimpour Soheil (Sciendo, 2018)
Background. Measuring the serum and alveolar procalcitonin level as inflammatory marker in the diagnosis of ventilator-associated pneumonia (VAP) has been taken into account. In this study, serum and alveolar procalcitonin levels in patients with suspected VAP and patients with confirmed VAP were compared.